2008
DOI: 10.2169/internalmedicine.47.1284
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Significances of Human T-cell Lymphotropic Virus Type I-Associated Myelopathy with T2 Hyperintensity on Spinal Magnetic Resonance Images

Abstract: Objective To clarify the incidence and clinical significance of HTLV-I associated myelopathy/tropical spastic paraparesis (HAM/TSP) showing T2 hyperintensity in the spinal cord on magnetic resonance images (MRI). Patients and Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
1
22
2
Order By: Relevance
“…In most cases of patients infected with HTLV-1, spinal cord MRIs are normal (58%). Atrophy of the cervical and thoracic segments are present in 34% of cases, and only 8% of cases show hyperintense lesions on the spinal cord on T2-weighted sequences, as presented in our patient 33. The incidence of brain MRI abnormalities in patients with HAM/TSP is common (25–80%).…”
Section: Discussionsupporting
confidence: 43%
“…In most cases of patients infected with HTLV-1, spinal cord MRIs are normal (58%). Atrophy of the cervical and thoracic segments are present in 34% of cases, and only 8% of cases show hyperintense lesions on the spinal cord on T2-weighted sequences, as presented in our patient 33. The incidence of brain MRI abnormalities in patients with HAM/TSP is common (25–80%).…”
Section: Discussionsupporting
confidence: 43%
“…Indirect signals of atrophy were observed in 14% of MRI of the brain and only 3% of the spinal cord. The frequency of these changes has been variable in the literature: hyperintense lesions in brain (52.4% -84%) and in spinal cord (7.9%) [16][17][18][19][20] . Atrophy of the spinal cord occurred in 20-74% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Each type was associated with spinal swelling along with high intensity lesions, mainly located in the posterior columns, posterior horns, or lateral columns. Comparison of the clinical parameters, including the protein content, IgG level, and cell counts in the CSF of HAM/TSP patients with and without spinal lesions revealed that abnormal highintensity spinal lesions seen on T2-weighted images were reflective of active inflammation during the early stages of rapidly progressive HAM/TSP (16,18). In the present patient, fulminant myelopathy and abnormal spinal lesions detected by MRI may not be related to the early stages of HTLV-I-associated neurological manifestations.…”
Section: Discussionmentioning
confidence: 99%